Few Patient, Treatment, and Diagnostic or Microbiological Factors, Except Complications and Intermittent Negative Cerebrospinal Fluid (CSF) Cultures During First CSF Shunt Infection, Are Associated With Reinfection - Simon, Tamara D. (Oxford University Press, 2014)
BACKGROUND: The relationship between first and subsequent cerebrospinal fluid (CSF) shunt infections is poorly understood. By understanding the factors associated with increased risk of reinfection, researchers may provide optimal treatment strategies at the time of first infection. The objective of this study was to describe and compare children with and without CSF shunt reinfection. METHODS: A retrospective cohort study was performed among 118 children who underwent initial CSF shunt placement and developed first CSF shunt infection. The primary outcome variable was CSF shunt reinfection. Patient risk factors and medical and surgical management of initial CSF shunt placement and first CSF shunt infection were compared between children with and without reinfection. RESULTS: Of 118 children with first infection, 31 (26%) developed a reinfection during the study period (overall median follow-up, 2096 days). Factors associated with reinfection in this cohort included ventriculoatrial or complex shunt at initial CSF shunt placement, complications after first CSF shunt infection, and intermittent negative CSF cultures. CONCLUSIONS: Few patient or treatment factors were associated with reinfection. Factors associated with difficult-to-treat first CSF shunt infection, including complications after first CSF shunt infection and intermittent negative CSF cultures, were associated with reinfection. Clinicians who treat patients with unusual CSF shunts or more difficult first infections should have a high index of suspicion for reinfection after treatment is completed.